Using self- and peer-assessment to enhance students’ future-learning in higher education. - Thomas, Glyn; Martin, Dona; Pleasants, Kathleen (Journal of University Teaching and Learning Practice, 2011)
In higher education settings, assessment tasks get the attention of students, but once students submit their work they typically become disengaged with the assessment process. Hence, opportunities for learning are lost as they become passive recipients of assessment outcomes. Future-learning oriented assessment engages students in the assessment process to improve both short- and long-term outcomes by requiring students to make sophisticated judgments about their own learning, and that of their peers. In this paper, we describe and critique three initiatives that experimented with future-learning oriented assessment within a faculty of education. These initiatives involved self- and peer-assessment in a mathematics education subject for first year pre-service teachers; peer assessment of individual contributions in a group project using a Wiki; and self- and peer-assessment to help students learn about leadership. Based on our experiences, we conclude with suggestions of how others might also use self- and peer-assessment to work towards better short- and long-term learning outcomes in higher education.